Measuring Mental Model of Primary Teachers and Pre-service Teachers on Heat Transfer Concept - Neni Hermita; Tommy Tanu Wijaya; Zetra Hainul Putra; Novi Yani Yora; Andi Suhandi (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study compares primary teachers' mental models with pre-service primary school teachers' mental models on the heat transfer concept. The mental model categories reviewed in this study include scientific, synthetic, and initial. This study's method was descriptive quantitative method, with research subjects 40 primary teachers and 40 pre-service primary teachers. This study's instrument is a conceptual understanding test consisting of three parts of a statement that asks for an explanation and description. The results showed that in understanding concepts test in synthetic mental models, 32.5%. In the category of initial mental models, there is a comparison of 32.5%. While in the concept of convection, there is a comparison of 2.5% in the scientific category. For synthetic mental models' category is 5%. In the category of initial mental models is 7.5%. For the concept of radiation, there is no comparison in the category of scientific mental models. Next there is a comparison of 7.5% in the category of synthetic mental models. In the category of initial mental models is 7.5%. Generally, elementary school teachers and students are in synthetic mental models and the initial mental models' category.